Minor tranquillisers and road accidents. - Skegg, D; Richards, S; Doll, R (1979)
In a prospective study of 43,117 people, prescriptions issued by general practitioners over two years were linked with records of hospital admissions and deaths. For 57 people injured or killed while driving cars, motorcycles, or bicycles the medicines that had been dispensed in the three months before were compared with those dispensed for 1,425 matched controls. There was a highly significant association between use of minor tranquillisers and the risk of a serious road accident (relative risk estimate 4.9). the increased risk of accidents to drivers given tranquillisers could be due to the known psychomotor effects of these drugs or to effects of the conditions being treated. Whatever the reason, patients taking drugs such as diazepam should be warned that they are at special risk.